Milenial Intention on Social Media - Selfia Ratna Kasih; Asep M Ramdan; Acep Samsudin (Journal of Management and Bussines (JOMB), 2020)
The purpose of this study is to measure how much influence social media Instagram and consumer confidence in millennial purchase interest. The variables of this research are Instagram social media (X1), consumer trust (X2) and millennial purchase interest (Y). The method used in this study is a quantitative research method with an associative approach, by distributing 200 online questionnaires to millennials of productive age. The analysis technique used to test the hypothesis in this study is the path analysis. Hypothesis test results show intagram social media and consumer trust have a significant influence on millennial buying interest and mediation hypothesis testing results show that consumer confidence variables mediate Instagram social media on millennial buying interest. Conclusion, consumer confidence in an online fashion store will certainly affect the buying interest. Keywords: Instagram, Consumer Trust, Social Media, Millennials, Purchase Interest